Preliminary results of the Pilot Project «Development of the Medical Rehabilitation System in the Russian Federation» in the city hospital № 26 (Saint Petersburg). Using «ICF reader» and the International Classification of Functioning for Setting Rehabili - A. A. Shmonin; M. N. Maltseva; V. V. Nikiforov; E. V. Melnikova; G. E. Ivanova; V. I. Dorofeev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
This article focuses on the implementation of the pilot project «Development of the medical rehabilitation system in the Russian Federation» in the city hospital № 26 (Saint Petersburg). By the experience of rehabilitation of stroke patients at the 1 stage, we analyzed the use of ICF for the purpose of setting a rehabilitation diagnosis and management of the rehabilitation process using the program «ICF-reader». We identified key issues and errors of ICF use in rehabilitation diagnosis. The article presents data on the frequency of using the different ICF domains in practice of rehabilitation. In this paper, we analyzed the average time of inspection of one patient by multidisciplinary team at admission to rehabilitation of the 1st and 2nd stages. The average time of examination was 10 [9; 13.5] minutes (median [percentile 25 %; 75 %]). Thus, the inspection of one patient needs of 5 to 15 minutes. During this period, the team has time to examine and discuss the patient, to make a diagnosis rehabilitation, to assign responsible specialists from the team and to make a rehabilitation plan for a week, to solve the issue of the rehabilitation potential and future patient routing. The introduction into rehabilitation process for stroke patients of such notion (tool) as rehabilitation diagnosis in terms of ICF fundamentally changes the nature of work of the rehabilitation team. Compliance with the «new» model of rehabilitation through implementation of the rehabilitation diagnosis and rehabilitation plan encourages the rehabilitation team to implement the basic principles of modern rehabilitation: the biopsychosocial model of disease, multidisciplinary principle, patientcentered principle, problemoriented approach and personalized principle. Implementation of the principle of the multidisciplinary team’s work and the use of the «ICFreader» leads to time reduction and intensification of the rehabilitation process.